Changing illness perceptions in poorly controlled Type 2 diabetes : a randomised controlled trial of a psychological, family-based intervention - Keogh, Karen (Trinity College (Dublin, Ireland). Department of Public Health and Primary Care, 2009)
Poor glycaemic (blood sugar) control in type 2 diabetes is associated with the development of microvascular and macrovascular complications, which have serious health and quality of life implications for patients themselves, as well as significant cost implications for healthcare providers. Patients with poorly controlled type 2 diabetes have been found to have significantly more inaccurate and negative beliefs or ‘perceptions’ about their illness, and report higher levels of emotional distress, when compared to those with good glycaemic control (White, Smith, & O'Dowd, 2001 -2004). These individual illness perceptions are a central component of an important theoretical framework in health psychology; Leventhal’s Self-Regulatory Model. A psychological intervention was developed to change the illness perceptions of patients with poorly controlled type 2 diabetes, with a view to improving their glycaemic control and psychological well-being. Family members were included in the intervention, as most diabetes management occurs in the home, and as such, may be influenced by, and impact upon, family relationships.
Keywords: Public Health and Primary Care, Ph.D.; Ph.D. Trinity College Dublin